Value at risk using smoothing techniques: a proposal in the foreign exchange market (Dimensión Empresarial, 2018)
One of the main problems that are exposed companies and financial institutions in Mexico is the volatility in the exchange rate Peso/Dollar when operating or in the valuation of financial assets. This article analyzes and compares the behavior of value at risk [VAR] under three different methodologies: historical simulation, Monte Carlo Simulation and straightening. An application to the exchange rate in periods of Precrisis, Postcrisis and economic crisis of 2008 is performed to look at the implications of the VAR calculation. We conclude that the straightening VAR methodology is more accurate.
Keywords: Exchange rate volatility; VAR; Monte Carlo Simulation